Level of electronic communication skills in Computer and Information Technology Curriculum by Middle School Students in the Kingdom of Saudi Arabia - Almohammadi, Najwa Atyan; Alharbi, Arwa Saleh Dakhil (Journal of Educational and Psychological Sciences, 2022)
The study aimed to identify the Level of electronic communication skills in Computer and Information Technology Curriculum by Middle School Students in the Kingdom of Saudi Arabia). In order to achieve these objectives, the researcher adopted the descriptive survey method in (12) items. She utilized the questionnaire as a study tool and it has been applied to a sample of (102) computer teachers of the intermediate school in Medina. The study concluded sever results, including: The mastery degree of electronic communication skills by the middle school students as (good) in general with a mean of (3.81 out of 5.00). In terms of these results, the study provided several recommendations, including: It is necessary to encourage teachers to enhance the abilities of their students and encourage them to continuously enter educational platforms, participate in virtual classes, activate discussion forums and guide them to the optimal use of e-learning.